Proses Permohonan Hak Pakai atas Tanah Milik Pribadi oleh Warga Negara Asing - I Komang Andi Darmawan; Anak Agung Sagung Dewi; I Putu Gd Seputra (Warmadewa Press, 2020)
This study aims to determine the process of application for usage rights on private land by foreign citizan in Indonesia which is in accordance with the Regulations in force in Indonesia that have been established by law No. 5 of 1960 concerning the rules of the basic principles of agrarian, and also Government Regulation No. 40 of 1996 concerning right to build, right to use, and right to use, as well as registration of land which is regulated in Government Regulation No. 24 of 1997. This research is based on normative legal research that is technical or applied. This research approach also uses a law approach and a case approach that has/is happening. Types of data in this study are primary and secondary legal materials. This data collection technique is carried out in the form of literature study and data analysis techniques used are deduction with the syllogism method. The results of this study indicate that foreign nationals residing in Indonesia can have rights to use land in Indonesia in the form of building use rights, use rights and business use rights, in which foreign citizens are given time limits in owning or using on land in Indonesia, so that there is no occurrence of foreign nationals who can own or buy land in Indonesia on behalf of these foreigners, we know that land in Indonesia is only intended for Indonesian citizens.